2015
DOI: 10.1097/meg.0000000000000353
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant presentation of autoimmune hepatitis

Abstract: Patients with F-AIH have a more indolent presentation compared with the non-F-AIH population. Altogether, only eight (20%) patients presenting with F-AIH survived without LT. A subset of patients with F-AIH and an initial MELD score less than 27 and low-grade hepatic encephalopathy might benefit from administration of corticosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 24 publications
0
22
0
5
Order By: Relevance
“…Patients presenting with AIH can benefit from the early use of corticosteroids. Although the risks and benefits of corticosteroid administration in this setting should be weighed carefully, prompt diagnosis and treatment of these patients might preclude LT or death …”
Section: Discussionmentioning
confidence: 99%
“…Patients presenting with AIH can benefit from the early use of corticosteroids. Although the risks and benefits of corticosteroid administration in this setting should be weighed carefully, prompt diagnosis and treatment of these patients might preclude LT or death …”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune hepatitis (AIH) is a complex disease characterized by immune-mediated destruction of hepatic parenchyma, female gender bias, presence of auto-antibodies, hypergammaglobulinaemia, association with other autoimmune conditions, and excellent response to immunosuppressive therapy[ 1 ]. Since its first description by Waldenström in the early 1950’s, AIH was considered to manifest as a chronic liver disease and its fulminant presentation was not commonly reported[ 2 - 4 ]. Over the last decades, it has become apparent that AIH can occur with diverse clinical phenotypes and its classical perception of a chronic inflammatory liver disease that affects mainly young Caucasian women has been expanded[ 5 - 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Infectious triggers are commonly indicated as being involved in the induction of autoimmune diseases, with Epstein-Barr (EBV) or Cytomegalovirus (CMV) being implicated in several autoimmune liver disorders, such as type I autoimmune hepatitis or primary biliary cholangitis (PBC)[ 9 ]. A remarkable proportion of patients with acute manifestation can develop acute liver failure (ALF), particularly in case of delayed diagnosis and treatment[ 4 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prognostic classifications are still not available for this high risk group, yet are key as severity of liver failure may play a role in steroid responsiveness (48). In fact, a study of 40 South American patients with a fulminant AIH revealed that corticosteroid failure was much more likely among those with higher MELD scores and encephalopathy grade 3 or higher (49). Utilization of corticosteroids in an acute severe presentation, preferably at high dose intravenously, requires close observation of clinical improvement or deterioration and infection.…”
Section: Acute Severe Presentationmentioning
confidence: 99%